How parents' beliefs and expectations influence their investments in children's early learning environments a social exchange perspective - Fetalvero, Abigaiel F. (Ann Arbor Michigan ProQuest LLC, 2011)
Children's early learning environments (i.e., home and child care) influence their school readiness, and parent's investments in these environments help shape children's experiences. Using data from the Early Childhood Longitudinal Study - Birth cohort (ECLS-B), a nationally representative sample of children born in 2001, this study investigates the relationships between parents' academic-related beliefs and expectations and their parenting investments in early learning environments (i.e., use center-based care, quality of child care learning environment, preference for care that prepares children for kindergarten, parent involvement, and quality of the home learning environment). Social exchange and social equity theories are used to frame the study. A series of hierarchical linear regression models indicates that parents' educational expectations are predictive of most indicators of investment except for parent involvement, whereas parents' beliefs about their child's readiness for school were predictive of parents' choice of quality of child care learning environment. The implications of these results for programs aimed towards parents as well as for further research are discussed.--Abstract.
Thesis (M.S.)--University of North Carolina at Greensboro, 2010.
Keywords: Early childhood education -- Parent participation; Parent and child